2005
DOI: 10.1111/j.1600-0846.2005.00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Depth profile of diffuse reflectance near‐infrared spectroscopy for measurement of water content in skin

Abstract: The correlations between the water contents measured by the optical and capacitance techniques were discussed. The dependencies of the light penetration depth on the source-detector geometry and wavelength are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 15 publications
(15 reference statements)
0
73
0
Order By: Relevance
“…However, the beam path length in media is highly influenced by wavelength since optical properties such as scattering and absorption coefficients and anisotropy parameters are the functions of wavelength. Previous studies 33 have concluded that the water bands at 1450 and 1900 nm visible in skin spectra have different absorption coefficients, and, therefore, have a different measurement depth. The water band around 1900 nm was shown to have a higher absorption coefficient, resulting in a shorter measurement in comparison to the band near 1450 nm since photons lose their energy more rapidly in the spectra range of strong water absorption.…”
Section: Resultsmentioning
confidence: 99%
“…However, the beam path length in media is highly influenced by wavelength since optical properties such as scattering and absorption coefficients and anisotropy parameters are the functions of wavelength. Previous studies 33 have concluded that the water bands at 1450 and 1900 nm visible in skin spectra have different absorption coefficients, and, therefore, have a different measurement depth. The water band around 1900 nm was shown to have a higher absorption coefficient, resulting in a shorter measurement in comparison to the band near 1450 nm since photons lose their energy more rapidly in the spectra range of strong water absorption.…”
Section: Resultsmentioning
confidence: 99%
“…The interrogation volume of these probes is defined in part by the spacing between the source and detector fibers. 37 Fiber-probe-based methods enable interrogation of ex vivo and in vivo intact tissues because, unlike integrating sphere setups, these methods typically employ measurement geometries that can be approximated as semi-infinite by radiative transport modeling approaches and thus do not require concurrent reflectance and transmittance measurements or an a priori knowledge of sample thickness. These fiber-based systems can also be employed preclinically or clinically due to their portable, flexible, and minimally invasive nature.…”
Section: Introductionmentioning
confidence: 99%
“…13 Many studies have investigated the sampling depth in scattering media both experimentally and numerically. [12][13][14][15][16] Most of these studies rely on the diffusion approximation, which is not valid for short SDSs and highly absorbing media. Others investigated the sampling depth only for reflectance probes with specific geometries, such as single-fiber reflectance, 16 overlapping illumination and collection areas, 17,18 large SDSs (SDS > 1∕μ 0 s ), 19 and diffuse reflectance spectroscopy probes only at specific SDSs and fiber diameters.…”
Section: Introductionmentioning
confidence: 99%
“…The light penetration depth depends not only on the absorption and scattering properties of the tissue, but also on the geometry of the diffuse reflectance probe. 12 Because of this, the depth sampling of a DRS probe can be tuned by adjusting the probe geometry, allowing for the design of application specific probes. 13 Many studies have investigated the sampling depth in scattering media both experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%